2004
DOI: 10.1021/ja046633l
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Helicity Induction on a Poly(phenylacetylene) with C2-Symmetric Chiral [60]Fullerene-Bisadducts

Abstract: Three chiral N-methylfulleropyrrolidine bisadducts were prepared, isolated, and completely resolved into each enantiomer using a chiral HPLC column, which were then converted to the corresponding optically active, cationic C(60)-bisadducts to investigate if they could act as a macromolecular helicity inducer in a poly(phenylacetylene) bearing an anionic monoethyl phosphonate pendant (poly-1) in aqueous solution. Upon complexation with the chiral C(60)-bisadducts, only the trans-3 bisadduct exhibited the charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 31 publications
1
60
0
Order By: Relevance
“…[19,20] Furthermore, when a cycloaddition reaction forms a bis-adduct with identical and symmetrical addends, some of the bis-adducts are chiral and racemic mixtures are often obtained. [21][22][23][24] In particular, trans-2, trans-3 and cis-3 adducts are mixtures of enantiomers due to their inherently chiral addition pattern. Although there have been studies of fullerene bis-adducts with two different substituents, only a few reports describe mixed bis-adducts bearing a cyclopropane and a pyrrolidine addend.…”
Section: Resultsmentioning
confidence: 99%
“…[19,20] Furthermore, when a cycloaddition reaction forms a bis-adduct with identical and symmetrical addends, some of the bis-adducts are chiral and racemic mixtures are often obtained. [21][22][23][24] In particular, trans-2, trans-3 and cis-3 adducts are mixtures of enantiomers due to their inherently chiral addition pattern. Although there have been studies of fullerene bis-adducts with two different substituents, only a few reports describe mixed bis-adducts bearing a cyclopropane and a pyrrolidine addend.…”
Section: Resultsmentioning
confidence: 99%
“…Along with inherently chiral pristine fullerenes, optically active derivatives have been obtained by chiral induction from chiral starting reagents or after tedious and expensive HPLC separation from the racemic mixture [40]. The non-coordinating nature of fullerenes has hampered the use of asymmetric metal catalysis and, therefore, the employ of enantiopure fullerene derivatives has been limited to a few examples [42][43][44].…”
Section: Asymmetric Catalysis On Fullerenesmentioning
confidence: 99%
“…Yashima and coworkers 58 have published a series of studies on the construction of chiral fullerene supramolecular assemblies through non-covalent complexation. In 2004, they reported that only specific structures and geometries of chiral C 60 -bisadducts could induce the formation of helical supramolecular assemblies.…”
Section: Chiral Interaction-induced Morphological Changes In Smart Pomentioning
confidence: 99%